Immunohistochemistry in the distinction between malignant mesothelioma and pulmonary adenocarcinoma: a critical evaluation of new antibodies - Abutaily, A S (Copyright 2002 Journal of Clinical Pathology, 2002)
Aim: The value of immunohistochemical staining in differentiating between malignant mesothelioma and pulmonary adenocarcinoma was re-examined using newly available commercial antibodies, with the aim of increasing the sensitivity and specificity of diagnosis, and simplifying the antibody panel required. Methods: Forty one malignant mesotheliomas and 35 lung adenocarcinomas were studied. Commercial antibodies to calretinin, E-cadherin, N-cadherin, surfactant apoprotein A (SP-A), thyroid transcription factor 1 (TTF-1), thrombomodulin, and cytokeratin 5/6 were applied using the streptavidin–biotin–peroxidase complex procedure on formalin fixed, paraffin wax embedded tissue. Results: E-cadherin was expressed in all adenocarcinomas and in 22% of the mesotheliomas. TTF-1 expression was detected in 69% of the adenocarcinomas and none of the mesotheliomas. Positive staining with polyclonal anticalretinin was detected in 80% of the mesotheliomas and 6% of the adenocarcinomas. N-cadherin was expressed in 78% of mesotheliomas and 26% of adenocarcinomas. Thrombomodulin was expressed in 6% of the adenocarcinomas and in 53% of the mesotheliomas. Cytokeratin 5/6 expression was detected in 6% of the adenocarcinomas and 63% of the mesotheliomas. The results were compared with the standard laboratory panel for mesothelioma diagnosis: anticarcinoembryonic antigen (anti-CEA), LeuM1, BerEP4, and HBME-1. Conclusion: Of the antibodies used in this study, E-cadherin was 100% sensitive for pulmonary adenocarcinoma and TTF-1 was 100% specific for pulmonary adenocarcinoma. The application of these two antibodies alone was adequate for the diagnosis of 69% of adenocarcinomas and 78% of mesotheliomas. Where TTF-1 is negative and E-cadherin is positive, a secondary panel of antibodies, including BerEP4 and LeuM1 (CD15) and antibodies directed against CEA, calretinin, cytokeratin 5/6, thrombomodulin, and N-cadherin, is required for differentiation between malignant mesothelioma and pulmonary adenocarcinoma.